Use of the earth and growth of the population in the east of the state of Mexico - Aguilar-Sánchez, Genaro (2019)
The east of the state of Mexico in recent years has had a large growth of urban centers, changing the use of natural resources. The objective is to characterize the use of the land and relate it to the population growth, to diagnose the impact of the population in the microbasin of the Coatepec and El Manzano rivers. For the above, eight uses of the land were characterized. Being the agricultural use the most representative of the basin. Through digital orthophotos and images from Landsat 7 satellites, maps of land use were generated for the years 1999 and 2015. The results obtained were the reduction of hectares destined for use: agricultural, vegetation less dense and, wasteland; while hectares were increased for urban use, mine and scrub. The changes in land use are related to the population growth of the municipalities present in the east of the state of Mexico: Chicoloapan, Ixtapaluca and Texcoco, with a growth rate in percent of 10.87, 4.4 and 1.2 respectively. It is recommended to diversify the crops, implement a controlled grazing system in scrub areas, as well as a management plan for 800 hectares of forest. Establish containment works for the control of runoff and reduction of trawls in the Manzano and Coatepec rivers